Gottesquartett: Erzählungen eines Ausgewanderten - Roth, Patrick (Herder, 2020)
A writer's therapist dies, and he flies to L.A. to take part in the funeral with four stories that he has dedicated to her. While the city is threatened with fires, he reads these stories of Abraham, Samuel, Samson, and Paul. Roth includes these stories in this work